Gypsiferous Soil Analysis of Samara-Tikrit Area-Iraq - Weam H. Kadum (Journal of Global Pharma Technology, 2020)
The soil properties are an important parameter for architectural and structural design of structures. Samara-Tikrit area in Iraq is a tourist destination, so in the last decade a number of multistory buildings, roads, etc. have been constructed. This study investigates the properties of the soil to give a base data, which can be used for the future construction design. This work aims investigating the gypsiferous soils texture, mineralogy and to interpret their geotechnical characteristics in Samara-Tikrit area, Iraq. A total of thirteen (13) soil samples were taken of gypsiferous soils distributed on three (3) sites. The results of grain-size analysis show that mixture of sand with variable percentages of clay and the silt fractions. The soil profile in site 1 reflect that the upper (0.9) m. is of sandy clayey silt, whereas the lower (2) m. is of silty sandy clay. The deep soil is of silty and clayey sand that reach 4.5 in depth. Concerning the soil profiles in site 2 and 3 representing silty sandy clayin general and silt beds occur at site 3. The soils within the three sites are fine-grained, yellowish light brown, moderately to highly gypsum, ranging from friable to very hard gypsiferous soil. The results of thin section are indicating that gypsum ranges from 12.3-35.4 %; clay comprise 12.0-26.2 %, while calcite and dolomite are from 9.6- 23.2 %. Quartz and Chert grains are ranging from 11.3- 26.0 %. Feldspar is ranging between 9.3- 19.0 %, while rock fragments is ranging from 7.2-15.7%, with heavy minerals ranging from 0.8 -1.9%. The X-ray diffraction analysis reflects that non-clay type minerals are quartz, calcite, dolomite, gypsum and feldspar; while the clay minerals are chlorite, smectite, kaolinite, illite and palygorskite. The geotechnical properties results reflect that six samples (1a, 1c, 1d,2c, 2d, 3b) are classified as gypsiferous soil with less than 25% gypsum content and with less values of initial void ratio, coefficient of curvature, uniformity coefficient, collapse potential %, compression strength, cohesion, and plasticity index % while the other seven samples (1b,1e,2a,2b,2e,3a,3c ) are classified as highly gypsiferous soil with more than 25% gypsum content and with relatively higher values of initial void ratio, coefficient of curvature, uniformity coefficient, collapse potential %, compression strength, cohesion and plasticity index% .Keywords: Gypsiferous soil, Texture, Mineralogy, Samara-Tikrit area, Iraq.